2019
DOI: 10.1038/s41598-019-54307-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress-controlled decomposition routes in cubic AlCrN films assessed by in-situ high-temperature high-energy grazing incidence transmission X-ray diffraction

Abstract: The dependence of decomposition routes on intrinsic microstructure and stress in nanocrystalline transition metal nitrides is not yet fully understood. In this contribution, three Al0.7Cr0.3N thin films with residual stress magnitudes of −3510, −4660 and −5930 MPa in the as-deposited state were in-situ characterized in the range of 25–1100 °C using in-situ synchrotron high-temperature high-energy grazing-incidence-transmission X-ray diffraction and temperature evolutions of phases, coefficients of thermal expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The in situ high-energy high-temperature grazing incidence transmission X-ray diffraction (HE-HT-GIT-XRD) [21] experiments were performed at the P07B beamline of the PETRA III synchrotron source in Hamburg (D) in transmission geometry, using a pencil X-ray beam with a size of 400 μm × 100 μm and an energy of 87.1 keV. The samples were mounted into a DIL 805 dilatometer (TA Instruments) with the surface aligned with respect to the primary beam at an incident angle β of ∼2 deg.…”
Section: In Situ High-temperature High-energy X-ray Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in situ high-energy high-temperature grazing incidence transmission X-ray diffraction (HE-HT-GIT-XRD) [21] experiments were performed at the P07B beamline of the PETRA III synchrotron source in Hamburg (D) in transmission geometry, using a pencil X-ray beam with a size of 400 μm × 100 μm and an energy of 87.1 keV. The samples were mounted into a DIL 805 dilatometer (TA Instruments) with the surface aligned with respect to the primary beam at an incident angle β of ∼2 deg.…”
Section: In Situ High-temperature High-energy X-ray Diffractionmentioning
confidence: 99%
“…The heating and cooling rates were adjusted for receiving sufficient diffracted signal at the 2D detector, which can be revised together with further experimental details in Ref. [21] .…”
Section: In Situ High-temperature High-energy X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the decomposition temperatures of the metastable fcc-(Al 63.5 Cr 36.5 )N phase depends significantly on the stress level in the coatings. The decomposition process starts at the same compressive stress level of around 4.3 GPa for all coatings that were investigated [75].…”
Section: Thermal Phase Stability and Hardness After Annealingmentioning
confidence: 99%
“…For example, thick coating layers are at risk of peeling off if the stress state is too high, while high compressive stresses can be advantageous in interrupted cutting operations. The stress state has also been pointed out as a key determining factor for thermal stability and decomposition pathways [75].…”
Section: Control Of Coating Morphology Stress and Texturementioning
confidence: 99%